Ablation of persistent atrial fibrillation based on high density voltage mapping and complex fractionated atrial electrograms: A randomized controlled trial. Issue 31 (6th August 2021) - Hwang, Jongmin; Park, Hyoung-Seob; Han, Seongwook; Lee, Cheol Hyun; Kim, In-Cheol; Cho, Yun-Kyeong; Yoon, Hyuck-Jun; Chung, Jin wook; Kim, Hyungseop; Nam, Chang-Wook; Hur, Seung-Ho; Kim, Jin Young; et al.
Abstract: Introduction: Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) catheter ablation. However, a PVI alone has been considered insufficient for persistent AF. This study aimed to evaluate the efficacy of persistent AF ablation targeting complex fractionated atrial electrogram (CFAE) areas within low voltage zones identified by high-resolution mapping in addition to the PVI. Methods: We randomized 50 patients (mean age 58.4 ± 9.5 years old, 86.0% males) with persistent AF to a PVI + CFAE group and PVI only group in a 1:1 ratio. CFAE and voltage mapping was performed simultaneously using a Pentaray Catheter with the CARTO3 CONFIDENSE module (Biosense Webster, CA, USA). The PVI + CFAE group, in addition to the PVI, underwent ablation targeting low voltage areas (<0.5 mV during AF) containing CFAEs. Results: The mean persistent AF duration was 24.0 ± 23.1 months and mean left atrial dimension 4.9 ± 0.5 cm. In the PVI + CFAE group, AF converted to atrial tachycardia (AT) or sinus rhythm in 15 patients (60%) during the procedure. The PVI + CFAE group had a higher 1-year AF free survival (84.0% PVI + CFAE vs 44.0 PVI only, P = .006) without antiarrhythmic drugs. However, there was no difference in the AF/AT free survival (60.0% PVI + CFAE vs 40.0% PVI only, P = .329). Conclusion: Persistent AF ablation targeting CFAE areas within low voltage zones using high-density voltage mapping had a higher AF free survival than a PVI only. Although recurrence with AT was frequent in the PVI+CFAE group, the sinus rhythm maintenance rate after redo procedures was 76%.